PEMANFAATAN DIGITAL MARKETING BAGI GREENPRENEUR DI DESA PUNGGUR BESAR KABUPATEN KUBU RAYA - Lubis, Laila Nurfitrah; Siallagan, Debbie Yuari; Prestoroika, Era; Yudimamase, Adiyath Randy; Hidayati, Asri; Depriyani, Magdalena; Sari, Eka Mustika (LP2M STP Mataram, 2024)
Punggur Besar Village in Kubu Raya Regency, West Kalimantan, holds significant potential in both its local resources and flagship products, one of which is plates made from areca palm sheaths. The village's Greenpreneurs focus on environmentally conscious entrepreneurship, contributing positively to the environment while also addressing economic opportunities arising from environmental challenges. However, these Greenpreneurs still face obstacles in implementing digital marketing due to limited understanding and skills in utilizing information technology, as well as a lack of knowledge about e-commerce platforms that can be used to market their products. They have yet to incorporate the use of websites, social media, or other online marketing tools in their sales efforts. This Community Service Program (PKM) aims to equip Greenpreneurs with knowledge and skills in digital marketing to promote their products, offering practical training that can be applied within the Greenpreneur community. The methods used in this PKM include training and lectures from experts, discussions, brainstorming, and assistance throughout the activity. Participants benefit by gaining a deeper understanding of digital marketing and applying it to product promotion, leading to increased business revenue and empowering the community to leverage digital technology for business growth